Diterpenoids target SARS-CoV-2 RdRp from the roots of Euphorbia fischeriana Steud - Ruan, Ting; Xiang, Zheng-Rui; Zhang, Yun-Wu; Fan, Shi-Rui; Ren, Juan; Zhao, Qian; Sun, Xiao-Long; Wu, Shi-Li; Xu, Li-Li; Qiao, Miao; Jing, Chen-Xu; Hao, Xiao-Jiang; et al. (Frontiers in Plant Science, 2024)
Currently, the development of new antiviral drugs against COVID-19 remains of significant importance. In traditional Chinese medicine, the herb Euphorbia fischeriana Steud is often used for antiviral treatment, yet its therapeutic effect against the COVID-19 has been scarcely studied. Therefore, this study focuses on the roots of Euphorbia fischeriana Steud, exploring its chemical composition, antiviral activity against COVID-19, and the underlying basis of its antiviral activity. Ultimately, nine new ent-atisane-type diterpenoid compounds were isolated from Euphorbia fischeriana Steud, named Eupfisenoids A-I (compounds 1-9). The compound of 1 was established as a C-19-degraded ent-atisane-type diterpenoid. During the evaluation of these compounds for their antiviral activity against COVID-19, compound 1 exhibited significant antiviral activity. Furthermore, with the aid of computer virtual screening and microscale thermophoresis (MST) technology, it was found that this compound could directly bind to the RNA-dependent RNA polymerase (RdRp, NSP12) of the COVID-19, a key enzyme in virus replication. This suggests that the compound inhibits virus replication by targeting RdRp. Through this research, not only has our understanding of the antiviral components and material basis of Euphorbia fischeriana Steud been enriched, but also the potential of atisane-type diterpenoid compounds as antiviral agents against COVID-19 has been discovered. The findings mentioned above will provide valuable insights for the development of drugs against COVID-19.